Content validity of the scale Perceptions on Interpersonal Racial Discrimination in Brazilian Healthcare Facilities (Driss) - Santa Rosa, Patricia Lima Ferreira; Borges, Ana Luisa Vilela; Araújo, Edna Maria de (Saúde e Sociedade, 2021)
Aiming to elaborate and assess the content validity of the new scale Perceptions on Interpersonal Racial Discrimination in Brazilian Healthcare Facilities (Driss), we conducted a methodological study based on the Classical Test Theory. Initially, we had a pool of 49 items based on a comprehensive literature review, previous qualitative study, and recommendations from a research group on ethnicracial inequalities. To assess content validity, an experts committee was formed. Qualitative and quantitative criteria were used to ensure methodological rigor. After the evaluation of the Driss version 1 by the experts committee, 28 items were excluded; 10 others were fragmented and/or modified. Thus, Driss version 2 was developed and subjected to pre-test, which showed a need to include introductory questions to make it better understood by the target population regarding the objectives of the study. Subsequently, we elaborated Driss version 3, whose content aims to value perceptions and feelings experienced by individuals who suffered racial discrimination at healthcare facilities. The content validity of version 3 was assessed by the Content Validity Ratio, being considered satisfactory and ready for later construct validity valuation.